2019
DOI: 10.5194/bg-2019-73
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effects of grass leaf anatomy, development and light/dark alternation on the triple oxygen isotope signature of leaf water and phytoliths: insights for a new proxy of continental atmospheric humidity

Abstract: <p><strong>Abstract.</strong> Continental relative humidity (RH) is a key-climate parameter. However, there is a lack of quantitative RH proxies suitable for climate model-data comparisons. Recently, a combination of climate chamber and natural transect calibrations laid the groundwork for examining the robustness of the triple oxygen isotope composition (δ<sup>18</sup>O, δ<sup>17</sup>O)… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
1
1
0
Order By: Relevance
“…On the other hand, the plants in this study also demonstrated the highest silicophytolith contents with silicate fertilization, in agreement with studies on other plants (Faisal et al 2012;Hartley et al 2015;Henriet et al 2006;Jones and Handreck, 1967;Ma and Takahashi 2002), including sugarcane (Bokhtiar et al 2012;Ramouthar et al 2016;De Tombeur et al 2020). Although the silicophytolith content was determined at 42 DAT in the TVD leaves, Si deposition frequently started at the first developmental stage and continued during the remainder of the plant's life cycle (Alexandre et al 2019;Fernández Honaine et al 2013De Tombeur et al 2020). Therefore, the silicophytolith contents and their morphotypes could be used to explain the gas exchange response results, which were based on the same type of leaves (TVD).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…On the other hand, the plants in this study also demonstrated the highest silicophytolith contents with silicate fertilization, in agreement with studies on other plants (Faisal et al 2012;Hartley et al 2015;Henriet et al 2006;Jones and Handreck, 1967;Ma and Takahashi 2002), including sugarcane (Bokhtiar et al 2012;Ramouthar et al 2016;De Tombeur et al 2020). Although the silicophytolith content was determined at 42 DAT in the TVD leaves, Si deposition frequently started at the first developmental stage and continued during the remainder of the plant's life cycle (Alexandre et al 2019;Fernández Honaine et al 2013De Tombeur et al 2020). Therefore, the silicophytolith contents and their morphotypes could be used to explain the gas exchange response results, which were based on the same type of leaves (TVD).…”
Section: Discussionsupporting
confidence: 91%
“…However, more studies are needed in order to understand the effect of the silica deposition in stomata in physiological processes. Furthermore, silicification is a passive process that is a consequence of transpiration or senescence in several cells (Alexandre et al 2019;Kumar and Elbaum 2018;Kumar et al 2017a, b). However, the silicification of bilobates (short cells) commonly occurs by metabolic control, and there has not yet been any report describing the specific role of bilobates in plants (Strömberg et al 2016).…”
Section: Discussionmentioning
confidence: 99%